2021
DOI: 10.1186/s12913-020-06036-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal death surveillance and response in Tanzania: comprehensiveness of narrative summaries and action points from maternal death reviews

Abstract: Background Maternal deaths reviews are proposed as one strategy to address high maternal mortality in low and middle-income countries, including Tanzania. Review of maternal deaths relies on comprehensive documentation of medical records that can reveal the sequence of events leading to death. The World Health Organization’s and the Tanzanian Maternal Death and Surveillance (MDSR) system propose the use of narrative summaries during maternal death reviews for discussing the case to categorize c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
2
18
0
2
Order By: Relevance
“…It also confirms the findings from another study which showed that written summaries used in MDSR were not comprehensive. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also confirms the findings from another study which showed that written summaries used in MDSR were not comprehensive. 15 …”
Section: Discussionmentioning
confidence: 99%
“…It also confirms the findings from another study which showed that written summaries used in MDSR were not comprehensive. 15 The most important step of the MDSR system is the implementation of action plans. Even though the system did not have a systematic way of tracking implementation of each action plan, health providers and managers reported that most were implemented.…”
Section: Implications For the Systemmentioning
confidence: 99%
“…These experiences challenge the purpose of the MPDSR system and could put both patient and clinician safety at risk. Few other studies on the topic are available to date, and generally, the focus has been on maternal death reporting practices [14, 16,17]. Our study has sought to focus on the perinatal aspect of MPDSR, as perinatal deaths are perceived differently than maternal deaths [39].…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to implementation and the process of maternal death review have been subject to some research in Sub-Saharan African countries, including Ethiopia [10, [13][14][15][16][17][18]. The process of auditing and reviewing perinatal deaths has, however, received less attention.…”
mentioning
confidence: 99%
“…Every health facility in Tanzania that provides reproductive and child health services,, including assisting childbirth, implements the MPDSR system [ 14 ]. The standard procedures for MPDSR require that every maternal death and perinatal death occurring either at the facility or in the community be reported to the regional level through respective councils, followed by a detailed review of the cause of death [ 10 ].…”
Section: Introductionmentioning
confidence: 99%